Phytopathogenic nematode communities infesting Moroccan olive agroecosystems: impact of agroecological patterns - Salah‑Eddine Laasli; Mokrini, Fouad; Iraqi, Driss; Munqez J. Y. Shtaya; Amiri, Said; Dababat, Abdelfattah A.; Paulitz, Timothy; Khfif, Khalid; Lahlali, Rachid (Springer, 2024)
Background and aimsOlive trees are one of the most important crops in the Mediterranean, especially in Morocco, and they are vulnerable to various soil-borne pathogens that can cause significant yield losses and economic damage. This study aimed to investigate the diversity, abundance, and community composition of phytopathogenic nematodes in Moroccan olive agroecosystems, and to evaluate the impact of agroecological patterns on their abundance.MethodsSoil and root samples were collected from 13 olive-growing localities across 7 Moroccan regions (43 nurseries/22 orchards), and nematodes were ecologically assessed through the calculation of several diversity indices (e.g., Shannon Index, Evenness, and Plant Parasitic Index). In addition, the main nematode genera were evaluated in terms of soil types, irrigation regimes, and landscape complexity.ResultsThe obtained results revealed the presence of a diverse and complex community of phytopathogenic nematodes represented by 25 genera, including Meloidogyne, Pratylenchus, and Helicotylenchus among others. The abundance and diversity of nematodes varied significantly between the different regions and agroecological patterns, with higher densities observed in simple landscapes and higher irrigation regimes. Moreover, the community of dominant nematodes was influenced by soil types. Root-knot nematodes were the most prevalent in sandy soils, while root-lesion nematodes were significantly present in the clayish setting. The occurrence and severity of nematode damage were also correlated with the overall taxonomic richness shaped in different olive landscape modes.ConclusionThis study provides updated information and prospects into nematode sustainable monitoring and management in North African olive agroecosystems.